'Step Up' approach to the application of REBOA technology in a rural trauma system. Issue 1 (12th July 2019) - Vernamonti, Jack P; Holcomb, John; Mick, Nathan W; Falank, Carolyne; Ontengco, Julianne B; Rappold, Joseph; Sheppard, Forest Raymond
Abstract : Our group has developed a 'Step Up' approach to the application of Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) in a rural trauma system. This incorporates viewing REBOA as a spectrum of technology. Examples of REBOA technology use to improve outcomes and provision of our system's clinical practice guideline for the Step-Up application of REBOA technology in the care of trauma patients are presented.